Catalysis and photocatalysis by platinized titanium dioxide and other catalysts - Smallwood, Keith (1993)
The gas-phase, thermal hydrogenations of propene and cyclopropane over various titania-supported metal catalysts have been investigated. Catalysts were prepared either by a photodeposition or a thermal reduction method. Absolute initial hydrogenation rates were calculated from total gas pressure vs time measurements. The activities of all catalysts were found to be very dependent upon catalyst state, as modified by reductive or oxidative pretreatments. These results are discussed in terms of reversible strong metal-support interactions, initiated via hydrogen spillover. For 0.5 %mass Pt on Ti02, the order of reaction with respect. to hydrocarbon was 0.5. An adsorption mechanism involving the alkylidene species is proposed as one possible explanation of this result. A negative order of reaction with respect to hydrogen was recorded. A Langmuir-Hinshelwood mechanism, involving competitive adsorption of hydrocarbon and hydrogen at supported metal sites, is proposed. Differences in behaviour between catalysts prepared by photodeposition and the thermally-prepared catalyst were observed during the hydrogenation studies. These include different apparent activation energies, maximum reaction rates at differing propene: hydrogen ratios and irreversible degradation of all photodeposited catalysts during cyclopropane hydrogenation. These differences are taken as being strongly indicative of differences in supported metal morphologies, arising as a consequence of the preparative routes employed. Temperature programmed desorption and scanning electron microscopy studies were undertaken in an attempt to establish and characterise these potential morphological differences. Although the results of these studies were, at best, inconclusive, the possible nature of such supported metal morphological differences is discussed on the basis of available evidence generated within this and other, similar, studies. The liquid-phase photocatalytic dehydrogenation of propan-2-ol, using the same catalysts, was also briefly investigated. Variations in measured activation energies suggest that photodeposited catalysts in the 'as prepared' state are contaminated with variable levels of impurity residues, particularly chloride ions.